An Analysis Of Systematic Literature Review On The Development Of Islamic Oriented Instruments - Aziz, Azlisham Abdul; Mamat, Mohd Nor; Salleh, Daud Mohamed; Abdullah, Syarifah Fadylawaty Syed; Nordin, Mohd Norazmi (The journal of contemporary issues in business and government, 2021)
This study analyzes the systematic approach of the literature review on Islamic- oriented instruments developed. Based on a survey conducted by the researcher, it was found that 15 instruments had been developed in Malaysia based on Islamic theories, models and muslim scholars. Most of the instruments that have been developed involve students at school, university, youth, adolescents, school administrators, and the appreciation of religion and the religiosity of the Muslim community in general. The analysis of the instruments formulated in this study is appropriate as a reference for Islamic researchers or organizations engaged in quantitative research in the selection of legitimate and reliable instruments and meeting research needs.